Pastoral Sociology and Development Paradigm in Nepal - Khan, Najia (Patan Pragya, 2023)
The main objective of this study is to dissect development from the prospective of pastoral sociology. It's grounded on secondary data, numerous exploration papers, sociological occasional journals, library and demonstrated accoutrements, secondary information sources have formerly been used. Pastoral Sociology plays a vital part to understand the problems and results of pastoral society especially for the developing country like Nepal. The study reveals that because of the significance of pastoral sociology the literacy and tutoring of sociology has been started in Nepal. Now in present days, institute of husbandry, institute of forestry, irrigation systems etc has been enforced in the name of pastoral sociology. There is the great part of pastoral sociologist in poverty elevation fund, planning commission, pastoral megacity, department of road and original development training center. The policy makers, political leaders, development workers should give emphasis on the literacy, tutoring and new inquiries on pastoral sociology with connecting the development. Teaching the farmers about the products appropriate in the particular farms based on the quality of soil across Nepal can help the country to develop economically and ultimately it leads every concerned one to become independent financially by exporting the local products to the most promising markets at home and beyond. The possibility of commercial agriculture can amplify the possibility of economic growth. Therefore, the interconnection between these aspects must be comprehensively understood and for this government of Nepal must take initiatives.